“Liberais de alma”: socialização e identidade política de jovens na Paraíba - Salles, Tatiana (2020)
This thesis studies the trajectories of young individuals who claim to be liberals, in order to understand what is liberalism and how to build a liberal political identity, often associated with the right wing in Brazil. Thus, the research problem was to understand that type of young agent, revealing the affective and social dimensions with which they were socialized since their childhood and which makes up their path of association with liberalism. Therefore, we realized that the interlocutors' liberal identities were built within a socializing process acquired from their families, schools, neighborhoods, universities and the internet. This thesis assumes that political socialization takes place in a subtle way in the private sphere, since it is only in the space of common living and in everyday life that individuals are able to express themselves and act politically (MUXEL, 2014). The trajectories of the young people surveyed suggest patterns of sentiments acquired from their families, friends, or schools. In all cases, there is to some extent a background of progressive left wing ideas and this was essential in the socialization of liberal ideas and, later, in their political transformation. This denotes that political convictions are negotiated and renegotiated in personal relationships (MUXEL, 2014). This thesis is based on more than two years of ethnographic research in Campina Grande and on in depth interviews with each young liberal. The empirical research started in June 2016 and was extended until December 2018, following the transition of power between the left and the extreme right, a delicate political context marked by new arrangements and unpredictability. However, it was a significant moment for the liberal anti-fusionist political position, defended by young people in this situation, who argue that liberals should not merge with conservatives, because in doing so, they give up their principles, which are economic and individual freedom. From this understanding, the idea of a “true liberal” emerges, which supports a certain vigilance in relation to other self proclaimed liberals, denoting that liberalism is a significant issue in dispute and recently, in Brazil, it is being incorporated by agents that challenge the sociological view.